New Simulated Plasma for Assessing Solubility of Mineral Trioxide Aggregate - Samiei, Mohammad; Shahi, Shahriar; Aslaminabadi, Naser; Valizadeh, Hadi; Aghazadeh, Zahra; Vahid Pakdel, Seyyed Mahdi (Iranian Endodontic Journal, 2014)
Introduction:Solubility of mineral trioxide aggregate (MTA) is an important characteristic that affects other properties such as microleakage and biocompatibility. Distilled water (DW) has previously been used for solubility tests. This experimental study compared the solubility of MTA in DW, synthetic tissue fluid (STF) and new simulated plasma (SP). Methods and Materials: In this study, 36 samples of tooth-colored ProRoot MTA were prepared and divided into three groups (n=12) to be immersed in three different solutions (DW, STF, and SP). Solubility tests were conducted at 2, 5, 9, 14, 21, 30, 50, and 78-day intervals. The unequal variance F-test (Welch test) was utilized to determine the effect of solubility media and Games-Howell analysis was used for pairwise comparisons. The repeated-measures ANOVA was used to assess the importance of immersion duration. Results: Welch test showed significant differences in solubility rates of samples between all the different solubility media at all the study intervals (P<0.05) except for the 14-day interval (P=0.094). The mixed repeated-measures ANOVA revealed a significant difference in solubility rate of MTA in three different solutions at all time-intervals (P=0.000). Games-Howell post-hoc test revealed that all pairwise comparisons were statistically significant at all time-intervals (P=0.000). Conclusion: Based on the findings of this study, the long-term solubility of MTA in simulated plasma was less than that in synthetic tissue fluid and distilled water.